2016
DOI: 10.18632/oncotarget.8563
|View full text |Cite
|
Sign up to set email alerts
|

KDM1A promotes tumor cell invasion by silencing TIMP3 in non-small cell lung cancer cells

Abstract: Epigenetic regulation plays an important role in tumor metastasis. KDM1A is a histone demethylase specific for H3K4me2/me1 demethylation, and has been found to be overexpressed in many cancers, including non-small cell lung cancer (NSCLC). However, the role of KDM1A in lung cancer remains unclear. Here, we show that KDM1A promotes cancer metastasis in NSCLC cells by repressing TIMP3 (tissue inhibitor of metalloproteinase 3) expression. Consistently with this, overexpression of TIMP3 inhibited MMP2 expression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 35 publications
(33 reference statements)
2
42
0
Order By: Relevance
“…It was found that inhibition of LSD1, either by siRNA silencing or SP2509 blockade significantly suppressed cell proliferation, mediated by G1/S cell cycle arrest, along with the accumulation of H3K4me2. These results are consistent with a previous report in non-small cell lung carcinomas, demonstrating that downregulation of LSD1 suppressed cell proliferation and migration capacity 32 . In our mouse model study, SP2509 treatment induced a significant decrease of tumor volume and tumor weight without obvious toxicity.…”
Section: Discussionsupporting
confidence: 94%
“…It was found that inhibition of LSD1, either by siRNA silencing or SP2509 blockade significantly suppressed cell proliferation, mediated by G1/S cell cycle arrest, along with the accumulation of H3K4me2. These results are consistent with a previous report in non-small cell lung carcinomas, demonstrating that downregulation of LSD1 suppressed cell proliferation and migration capacity 32 . In our mouse model study, SP2509 treatment induced a significant decrease of tumor volume and tumor weight without obvious toxicity.…”
Section: Discussionsupporting
confidence: 94%
“…LSD1 is aberrantly upregulated in many human cancer types, such as prostate, breast and lung carcinoma as well as neuroblastoma and leukemia 12 16 . Importantly, cancer-related LSD1 overexpression is associated with increased cell proliferation, invasion and migration underscoring the therapeutic potential of LSD1 inhibition 13 , 16 , 17 . In a proliferation screen of cell lines representing various tumor types, acute myeloid leukemia (AML) and SCLC cell lines have been shown to be particularly sensitive to pharmacological LSD1 inhibitors, resulting in cytostatic growth inhibition and advanced differentiation 15 , 18 .…”
Section: Introductionmentioning
confidence: 98%
“…Egolf et al [65] reported that its downstream targets were involved in epidermal differentiation and cornification processes. Kong et al [66] indicated that treatment with KDM1A inhibitor (2-PCPA) reduced tumour NSCLC cell proliferation and migration. On the other hand, TP63 has been shown as a key player in homeostasis and development of squamous epithelium.…”
Section: Discussionmentioning
confidence: 99%